2014
DOI: 10.1134/s1061933x14050081
|View full text |Cite
|
Sign up to set email alerts
|

Heterocoagulation of polysaccharide-coated platinum nanoparticles with ovarian-cancer cells

Abstract: Platinum nanoparticles coated with adsorption layers of polysaccharides of Chlorella vulgaris (Pt PS ) have been synthesized and their heterocoagulation with human ovarian cancer cells of the A2780 line has been studied. It has been shown that the characteristic time of the aggregation of the cells with Pt PS nano particles is 20-25 min, which corresponds to fast barrierless coagulation. The cytotoxic effect of Pt PS nano particles reaches saturation and more than 50% of the cells die within this time period. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…It was found that the endocytosis was the driving mechanism for the penetration of nanoparticles through the cellular membrane in cells. [159] Ali et al, biosynthesized PtNPs (30-45 nm size) using Iraqi Zahidi dates as reducing agent. PtNPs effectively was investigated against SKO-3 Ovarian cells.…”
Section: Ptnps In Ovarian Cancer Treatmentmentioning
confidence: 99%
“…It was found that the endocytosis was the driving mechanism for the penetration of nanoparticles through the cellular membrane in cells. [159] Ali et al, biosynthesized PtNPs (30-45 nm size) using Iraqi Zahidi dates as reducing agent. PtNPs effectively was investigated against SKO-3 Ovarian cells.…”
Section: Ptnps In Ovarian Cancer Treatmentmentioning
confidence: 99%
“…The potent anticancer reagents of Ir-based compounds have triggered extensively interest as well [134,135]. In some studies, PGEbased nanomaterials have been explored as possible alternatives or associated with compounds for anticancer treatment [136][137][138][139][140][141]. However, researchers are developing more efficient treatments against tumors in consideration of the toxic effects of chemotherapies.…”
Section: Cancer Therapymentioning
confidence: 99%